Synthesis and Crystallization of Aluminum Sulfate from Kaolin as an Aluminum Source Using Bleaching Earth Activation Wastewater - Othman Azam Abia Musa; Mochammad Ilham Hanafi; Suprihatin Suprihatin; Sani Sani; Ely Kurniati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Liquid waste generated from bleaching earth activation typically contains sulfuric acid and various metal ions, which pose environmental concerns but also offer potential as precursors for value-added chemical products. However, the utilization of this waste as a source for aluminum sulfate production remains limited. This study investigates the synthesis of aluminum sulfate (Al?(SO?)?) from bleaching earth liquid waste of PT. Madu Lingga Raharja uses kaolin as an aluminum source through a leaching–crystallization process. The leaching reaction was carried out by reacting 250 mL of liquid waste with kaolin at 100 °C for 60 minutes, followed by evaporation, crystallization, ethanol washing, and drying. The effects of kaolin mass (60–100 g) and stirring speed (250–450 rpm) on aluminum extraction were evaluated. The resulting products were characterized using X-Ray Fluorescence (XRF) for elemental composition and Scanning Electron Microscopy (SEM) for crystal morphology. The results show that increasing kaolin mass and stirring speed significantly enhance aluminum extraction due to improved mass transfer and reduced diffusion layer thickness. The optimum condition was obtained at 100 g of kaolin and a stirring speed of 450 rpm, yielding an Al?(SO?)? concentration of 12.50%, compared to the initial concentration of 7.7% in the untreated waste. SEM observations confirmed the formation of crystalline aluminum sulfate with plate-like morphology. Although the synthesis process improved the aluminum sulfate concentration, the obtained Al?O? content still does not meet the specification required by SNI 0032:2011, indicating that further purification or process optimization is required. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation and InfrastructureSDG 13: Climate Action